Reflect, Assess, Visualize: Cultivating Skill Development in User Experience Education - Rose, Emma; Putnam, Cynthia; MacDonald, Craig (Design and Technology Education: An International Journal, 2024)
In the field of user experience (UX), there is a wide range of skills that practitioners are expected to acquire and demonstrate as a competitive candidate for a job. Previous research identified three main skill categories of UX practitioners: technical skills, human skills, and dispositions. However, as educators, we have found that students often struggle to understand and incorporate the breadth of the skills they need into their learning and development. To help students identify, assess, and cultivate their skill sets, we designed a pedagogical intervention in the form of an ‘advance organizer’ that asks students to reflect on their initial and changing skill sets while enrolled in a UX-focused course. In this article, we present the basis of the intervention, including background on learning theories that supported its design. The intervention asks students to read and reflect on an academic article about the desired skills of aspiring UX practitioners, conduct an inventory of their existing and desired skill sets, and design a visualization to represent their current and future skill levels. We report on how the intervention was implemented in three different programs related to UX (one undergraduate, and two graduate programs). An analysis of the resulting assignments suggests the intervention was effective and valuable and helped give students a better sense of the range of skills required in industry. We conclude with considerations for implementing the intervention.